2010
DOI: 10.1029/2009jc005402
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of storm surge, wave, currents, and inundation in the Outer Banks and Chesapeake Bay during Hurricane Isabel in 2003: The importance of waves

Abstract: [1] This paper investigates the effects of waves on storm surge, currents, and inundation in the Outer Banks and Chesapeake Bay during Hurricane Isabel in 2003 through detailed comparison between observed wind, wave, surge, and inundation data and results from an integrated storm surge modeling system, CH3D-SSMS. CH3D-SSMS, which includes coupled coastal and basin-scale storm surge and wave models, successfully simulated measured winds, waves, storm surge, currents, and inundation during Isabel. Comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 50 publications
(68 reference statements)
4
99
0
Order By: Relevance
“…Sheng et al [15] reported that the accuracy of a storm surge simulation depends on many factors including the input data (e.g., bathymetry, topography, and wind/pressure fields), the representation of important processes (e.g., flooding and drying and bottom friction), the model grid resolution, and the open boundary conditions. Simulating inundation is an important aspect of storm surge modeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheng et al [15] reported that the accuracy of a storm surge simulation depends on many factors including the input data (e.g., bathymetry, topography, and wind/pressure fields), the representation of important processes (e.g., flooding and drying and bottom friction), the model grid resolution, and the open boundary conditions. Simulating inundation is an important aspect of storm surge modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamic component of the modeling system was based on the Princeton Ocean Model, and a scheme with a multiple inundation speed option was embedded in the model for the inundation calculation. Sheng et al [15] investigated the effect of waves on storm surges, currents, and inundation in the Outer Banks, North Carolina and the Chesapeake Bay during Hurricane Isabel in 2003 by making a detailed comparison between the observed wind, wave, surge, and inundation data and the results from an integrated storm surge modeling system. Xie et al [20] used a three-dimensional storm surge model to study the effect of the asymmetric structure of a hurricane wind field on the storm surge and the inundation extent.…”
Section: Introductionmentioning
confidence: 99%
“…The sea surface drag coefficient formulation plays a key role in storm surge modeling (Nicolle et al 2009;Sheng et al 2010). According to shallow water equations which are the basis of the surge model and under some assumptions (1D uniform steady flow over a flat bed with wind directed to the coast, neglecting Coriolis effect), it is possible to analytically …”
Section: Sea Surface Drag Formulations and Comparisonmentioning
confidence: 99%
“…CH3D-SSMS (Storm Surge Modeling System) is a modeling suite that features coupled CH3D and SWAN models for coastal dynamics and large scale surge-wave models that are used to extract boundary conditions for the coastal model [11,17], which has been used extensively to simulate storm surge and inundation due to various tropical cyclones including Hurricanes Charley [11][12][13][17][18][19]. Details of the CH3D model, including equations of motion and boundary and initial conditions, are described in [11].…”
Section: Ch3d-ssmsmentioning
confidence: 99%